Indonesian Pluralism and Democracy Under Challenge: A Social Reflection - Herdi Sahrasad (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2016)
Islamic puritanism in Indonesia is getting more and more stronger. Such strong growth of Islamic Puritanism in Indonesia , as he furthered, is playing an important role of the spread of Islamic radical ideology. pluralism would be pushed aside by the conservative Islamic scholars and ulamas in Indonesia, included in Muhammadiyah and NU themselves. Muhammadiyah and NU, the two Islamic bastions for pluralism and tolerance, have been facing strong pressure from of puritant Islamists and fundamentalists who advocate ‘’transnational Islam’’ for the ummah. Indonesian state and society under liberal democracy are still facing uncertainty in the near future because the weakness of law enforcement and legal certainty, also the weakness of the national leadership under the tyranny of capital and oligarchs.